Preparation method and application of eleven-layer co-extruded high-barrier high-strength recyclable liquid packaging material

Through the eleven-layer composite structural film made of a single PE material, the composite material is formed by reacting heat-activated mica with intercalation modification reagent, which solves the problem of recycling and utilization of multi-layer coextruded films and realizes high-barrier and high-strength liquid packaging Materials, simplifying the recycling process and improving utilization.

CN118578745BActive Publication Date: 2024-12-13SUZHOU ZIJIN PLASTIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411075130.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2024-12-13
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

The existing multi-layer co-extruded films are difficult to recycle and utilize after use, resulting in environmental pollution and waste of resources. Multi-layer co-extruded films of a single material are classified in a complex manner and have low utilization rate during recycling.

Method used

The eleven-layer composite structure film of a single PE material is used to heat-activate mica and react with intercalation modification reagent to form an ethylene-vinyl alcohol copolymer/mica sheet composite material. The high barrier and high strength can be prepared by coextrusion blow molding process. Recycle liquid packaging materials.

Benefits of technology

The excellent barrier properties and mechanical properties of eleven layers of co-extruded materials are achieved, the recycling process is simplified, the recycling rate is improved, and environmental pollution is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118578745B_ABST
    Figure CN118578745B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of research and development of multifunctional packaging materials, and discloses a preparation method and application of an eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material, comprising: preparing an intercalation modification agent containing a secondary amine functional group; utilizing ammonium cations of the intercalation modification agent to undergo an ion exchange reaction with interlayer sodium cations of sodium mica and then adsorbing the intercalation modified mica on the surface of a mica sheet through electrostatic action to obtain an intercalation modified mica with a secondary amine functional group; dispersing the intercalation modified mica in an ethylene-vinyl alcohol copolymer matrix based on hydrogen bonding to obtain an ethylene-vinyl alcohol copolymer / mica sheet composite material; using polyethylene resin as a single raw material and an ethylene-vinyl alcohol copolymer / mica sheet composite material as a functional modification agent, and adopting an eleven-layer co-extrusion blow molding film-forming process to prepare an eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material with excellent barrier properties and mechanical properties, which can be applied in the field of liquid packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of research and development of multifunctional packaging materials, and specifically to a preparation method and application of an eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material. Background Art

[0002] Plastic packaging materials have been rapidly developed in the packaging industry due to their advantages of high strength, high barrier properties, light weight, and easy processing. They are widely used as packaging materials for food, cosmetics, medicines, express delivery, etc. However, the protective functions of single-layer plastic packaging films such as gas barrier (oxygen, carbon dioxide), light shielding, moisture resistance, and impact deformation resistance are limited and cannot meet people's growing living needs. Therefore, multi-layer composite films are highly favored in the packaging industry and the food industry and have good development prospects. The molding methods of multi-layer composite films are mainly divided into lamination, coating, and multi-layer co-extrusion. Among them, multi-layer co-extrusion technology and co-extrusion films have developed rapidly, and their usage has accounted for more than 1 / 3 of the total production of packaging films.

[0003] At present, multi-layer co-extruded films are usually made of a variety of raw materials of different materials, which makes the sorting and classification process after use cumbersome and difficult, and the recycling rate is low. Random discarding and improper disposal will cause serious environmental pollution and waste of resources. Multi-layer co-extruded films made of a single plastic material do not need to be classified when recycled, and can be 100% recycled and reused, which has gradually become a trend in the development of the multi-layer co-extruded film industry. For example, the Chinese invention patent application with publication number CN116604907A discloses a high-barrier recyclable composite film of a single material, which is composited with three layers of polyethylene materials. The single material is more conducive to recycling and is an environmentally friendly packaging material.

[0004] The present invention cites the following references:

[0005] 1. Jilin University's master's thesis "Synthesis and Performance Study of Polyaryletherketone Materials with Double-splint Structure Cage-type Silsesquioxane in the Main Chain" disclosed the chemical structure and preparation method of octaphenyl cage-type silsesquioxane (DDSQ).

[0006] 2. The Journal of Southwest Forestry University published an article entitled "Research on DOPO Derivatives / Octaaminopropyl POSS Flame-Retardant Wood-Plastic Composite Materials" by Zhang Ling et al. on pages 136-144 of Volume 43, Issue 3, May 2023, which disclosed the chemical structure and preparation method of octaaminopropyl POSS (OA-POSS). Summary of the invention

[0007] The present invention has developed a novel eleven-layer composite structure film of a single PE material. The eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material has very excellent barrier properties and mechanical properties and can be used in the field of liquid packaging.

[0008] A method for preparing an eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material, comprising the following steps:

[0009] Step 1: preparing an ethylene-vinyl alcohol copolymer / mica sheet composite material, wherein the preparation method of the composite material is as follows:

[0010] (1) Thermal activation and structural modification of sericite to obtain sodium mica;

[0011] (2) synthesizing an intercalation modification agent, wherein the intercalation modification agent is one or a combination of intercalation agent I, intercalation agent II, and intercalation agent III;

[0012] Wherein, intercalant I is a dibromide ammonium salt compound having a long main chain and a secondary amine functional group;

[0013] The intercalant II is a dibromide ammonium salt compound having a double-sandwich structure cage-type silsesquioxane and a secondary amine functional group on the long main chain;

[0014] Intercalant III is an octabromide ammonium salt compound with eight long side chains grafted onto POSS, a cage-type silsesquioxane with a highly symmetrical spatial structure, and the long side chains contain secondary amine functional groups;

[0015] (3) The ammonium cations of the intercalation modification reagent undergo ion exchange reaction with the interlayer sodium cations of the sodium mica and then adsorb onto the surface of the mica sheet through electrostatic action to prepare intercalation modified mica with secondary amine functional groups;

[0016] (4) dispersing the intercalated modified mica in the ethylene-vinyl alcohol copolymer, and combining the ethylene-vinyl alcohol copolymer with the mica sheet through hydrogen bonding between the secondary amine functional groups in the intercalated modified mica and the hydroxyl functional groups in the ethylene-vinyl alcohol copolymer, thereby preparing an ethylene-vinyl alcohol copolymer / mica sheet composite material;

[0017] Step 2: Using polyethylene resin as a single raw material and ethylene-vinyl alcohol copolymer / mica sheet composite material as a functional modification agent, design the film structure of the eleven-layer co-extruded film, the formula and dosage of each film layer, and adopt an eleven-layer co-extrusion blow molding film forming process to prepare an eleven-layer co-extruded high-barrier, high-strength recyclable liquid packaging material.

[0018] Preferably, the mass ratio of the intercalation modification agent to the sodium mica in the intercalation modified mica is (0.1-0.5):1;

[0019] Preferably, the particle size of the sericite is <10 μm.

[0020] Preferably, the mass ratio of intercalated modified mica to ethylene-vinyl alcohol copolymer in the ethylene-vinyl alcohol copolymer / mica sheet composite material is 1:(0.5-5).

[0021] Preferably, the content of the ethylene-vinyl alcohol copolymer / mica sheet composite material in the eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material is 0.5-2%.

[0022] Preferably, the formula and dosage of each film layer of the eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material are as follows:

[0023] First layer: The formula is 25~45wt% LDPE+25~45wt% LLDPE+10~50wt% m-LLDPE, and the dosage is 5~15wt%;

[0024] The second layer: the formula is 25~45wt%HDPE+20~40wt%LLDPE+15~55wt%m-LLDPE, the dosage is 3~10wt%;

[0025] The third layer: the formula is 10~30wt% LDPE+10~30wt% LLDPE+40~80wt% m-LLDPE, the dosage is 5~15wt%;

[0026] The fourth layer: the formula is 100wt% PE-g-MAH, the dosage is 1~5wt%;

[0027] The fifth layer: the formula is 95~99wt% LDPE+1~5wt% EVOH, the dosage is 5~15wt%;

[0028] The sixth layer: the formula is 90~99wt% LDPE+1~10wt% ethylene-vinyl alcohol copolymer / mica sheet composite material, the dosage is 10~40wt%;

[0029] The seventh layer: the formula is 95~99wt% LDPE+1~5wt% EVOH, the dosage is 5~15wt%;

[0030] The eighth layer: the formula is 100wt% PE-g-MAH, the dosage is 1~5wt%;

[0031] Ninth layer: The formula is 10~30wt% LDPE+10~30wt% LLDPE+40~80wt% m-LLDPE, and the dosage is 5~15wt%;

[0032] The tenth layer: the formula is 25~45wt%HDPE+20~40wt%LLDPE+15~55wt%m-LLDPE, the dosage is 3~10wt%;

[0033] Eleventh layer: The formula is 25~45wt% LDPE+25~45wt% LLDPE+10~50wt% m-LLDPE, and the dosage is 5~15wt%.

[0034] Preferably, the preparation method of the intercalant I is: using 1,3-propylenediamine and 1-bromo-6-(trimethylammonium)hexyl bromide as raw materials, and preparing the intercalant I by a substitution reaction between the bromine functional group of 1-bromo-6-(trimethylammonium)hexyl bromide and the amino functional group of 1,3-propylenediamine.

[0035] Preferably, the preparation method of the intercalant II is:

[0036] The synthetic amino-terminated octaphenyl cage silsesquioxane monomer is prepared by an addition reaction between the Si-H bond of the octaphenyl cage silsesquioxane and the alkenyl functional group of 3-butene-1-amine;

[0037] Using amino-terminated octaphenyl cage silsesquioxane monomer as a nucleophilic reagent, intercalant II is prepared by substitution reaction between the bromine functional group of 1-bromo-6-(trimethylammonium)hexyl bromide and the amino functional group of the amino-terminated octaphenyl cage silsesquioxane monomer.

[0038] Preferably, the preparation method of the intercalant III is: preparing the intercalant III by a substitution reaction between the bromine functional group of 1-bromo-6-(trimethylammonium)hexyl bromide and the amino functional group of octaaminopropyl POSS.

[0039] The thickness of the eleven-layer co-extruded high-barrier, high-strength and recyclable liquid packaging material prepared according to the above method is 50-200 μm.

[0040] The application of an eleven-layer co-extruded high-barrier, high-strength recyclable liquid packaging material prepared according to the above method in the field of liquid packaging.

[0041] Beneficial effects: The present invention independently developed and synthesized the following intercalation modification reagents:

[0042] Intercalants I with longer main chains and secondary amine functional groups;

[0043] Intercalant II containing a double-splint structure cage-type silsesquioxane and a secondary amine functional group on a longer main chain;

[0044] Intercalant III grafted with eight relatively long side chains and highly symmetrical cage-type silsesquioxane (POSS) and containing secondary amine functional groups;

[0045] Thermal activation and structural modification (acidification and sodiumization) of sericite are performed to make the sericite have interlayer ion exchangeability and obtain sodiumized mica;

[0046] Using an intercalation modification agent to perform intercalation modification treatment on sodium mica to obtain intercalation modified mica with secondary amine functional groups;

[0047] The secondary amine functional groups of the intercalated modified mica and the hydroxyl functional groups contained in the ethylene-vinyl alcohol copolymer are hydrogen-bonded to achieve the combination of the inorganic mica material and the ethylene-vinyl alcohol copolymer, that is, to obtain the ethylene-vinyl alcohol copolymer / mica sheet composite material;

[0048] The 11-layer co-extruded high-barrier and high-strength recyclable liquid packaging material is prepared by modifying a single recyclable PE material using an ethylene-vinyl alcohol copolymer / mica sheet composite material;

[0049] The experimental results show that the eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material has excellent barrier properties and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 is the chemical structural formula of intercalant Ⅰ;

[0051] Figure 2 is the chemical reaction formula of amino-terminated octaphenyl cage silsesquioxane monomer;

[0052] Figure 3 is the chemical structural formula of intercalant II;

[0053] Figure 4 is the chemical structural formula of intercalant III;

[0054] Figure 5 These are the performance test results of eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging materials. DETAILED DESCRIPTION

[0055] The present invention uses inorganic nanomaterials (nanomica sheets) and high molecular polymers (ethylene-vinyl alcohol copolymers) as modifying agents for a single recyclable material;

[0056] Mica clay minerals with interlayer cations have narrow interlayer domains where the interlayer cations are located. Studies have found that it is difficult for organic ion groups to enter the interlayers for exchange reactions. Based on this, the present invention first performs thermal activation and structural modification (acidification and sodiumization) on sericite to allow the sericite to obtain interlayer ion exchangeability, then uses an intercalation modification reagent independently developed to perform intercalation modification treatment on the sericite, and finally combines it with ethylene-vinyl alcohol copolymer to form an organic-inorganic composite material. Embodiment 1:

[0057] Preparation of intercalant I: Using 1,3-propylenediamine and 1-bromo-6-(trimethylammonium)hexyl bromide as raw materials, the bromine functional group of 1-bromo-6-(trimethylammonium)hexyl bromide and the amino functional group of 1,3-propylenediamine undergo a substitution reaction to generate intercalant I, whose chemical structure is as follows: Figure 1 As shown;

[0058] The specific experimental steps for preparing intercalation agent I are as follows: 0.8 g of 1,3-propylenediamine, 1.1 g of sodium bicarbonate and 30 mL of N,N-dimethylformamide are added to a three-necked flask, and dissolved at room temperature for 1 h under nitrogen protection and mechanical stirring, and then 50 mL of 1-bromo-6-(trimethylammonium)hexyl bromide solution (prepared by dissolving 6.1 g of 1-bromo-6-(trimethylammonium)hexyl bromide in 50 mL of N,N-dimethylformamide) is added dropwise to the three-necked flask, and the temperature is raised to 40° C. and stirred for 10 h, and the solvent is removed by rotary evaporation, and the intercalation agent I is obtained after vacuum drying;

[0059] The results of H NMR characterization of intercalant Ⅰ are as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 1.35-1.52 (m, 8H), 1.63-1.80 (m, 10H), 2.55-2.60 (m, 4H), 2.76-2.81 (m, 4H), 3.18-3.24 (m, 2H), 3.43 (s, 18H), 3.50-3.53 (t, 4H). Embodiment 2:

[0060] Prepare intercalant II, the preparation process is as follows:

[0061] (1) Synthesizing an amino-terminated octaphenyl cage silsesquioxane monomer, wherein the synthesis method is as follows: an addition reaction is carried out between the Si-H bond of octaphenyl cage silsesquioxane (DDSQ) and the alkenyl functional group of 3-butene-1-amine to generate an amino-terminated octaphenyl cage silsesquioxane monomer, wherein the chemical reaction formula is as follows: Figure 2 As shown, the specific experimental steps are as follows: add 5.8g of octaphenyl cage silsesquioxane and 50mL of toluene to a three-necked flask under nitrogen protection, heat to 35°C and stir until all dissolved, then drop 10mL of 3-butene-1-amine solution (prepared with 0.7g of 3-butene-1-amine and 10mL of toluene) and 4 drops of Custer catalyst to the three-necked flask in sequence, heat to 80°C and stir to react for 24h, cool to room temperature, remove the solvent by rotary evaporation, and vacuum dry to obtain an amino-terminated octaphenyl cage silsesquioxane monomer;

[0062] (2) Synthesis of intercalant II: using an amino-terminated octaphenyl cage silsesquioxane monomer as a nucleophilic reagent, and reacting the bromine functional group of 1-bromo-6-(trimethylammonium)hexyl bromide with the amino functional group of the amino-terminated octaphenyl cage silsesquioxane monomer to generate an intercalant II, the chemical structure of which is as follows: Figure 3 As shown, the specific experimental steps are as follows: 6.5 g of amino-terminated octaphenyl cage-type silsesquioxane monomer, 0.8 g of sodium bicarbonate and 80 mL of N, N-dimethylformamide are added to a three-necked flask, dissolved at room temperature for 1 h under nitrogen protection and mechanical stirring, and then 20 mL of 1-bromo-6-(trimethylammonium)hexyl bromide solution (prepared by dissolving 3.0 g of 1-bromo-6-(trimethylammonium)hexyl bromide in 20 mL of N, N-dimethylformamide) is added dropwise to the three-necked flask, the temperature is raised to 40° C. and stirred for reaction for 8 h, the solvent is removed by rotary evaporation, and intercalation agent II is obtained after vacuum drying;

[0063] The nuclear magnetic resonance hydrogen spectrum characterization results of intercalant II are as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 0.09 (s, 6H), 0.89-0.92 (t, 4H), 1.31-1.51 (m, 16H), 1.65-1.80 (m, 8H), 2.67-2. 85(m, 8H), 3.37-3.42(m, 2H), 3.43(s, 18H), 3.49-3.53(t, 4H), 7.33-7.54(m, 40H). Embodiment 3:

[0064] Preparation of intercalant III: The bromine functional group of 1-bromo-6-(trimethylammonium)hexyl bromide and the amino functional group of octaaminopropyl POSS (OA-POSS) undergo substitution reaction to generate intercalant III, whose chemical structure is as follows: Figure 4 As shown;

[0065] The specific experimental steps for preparing intercalant III are as follows: 4.4 g of octaaminopropyl POSS, 1.5 g of sodium bicarbonate and 50 mL of N, N-dimethylformamide are added to a three-necked flask, and dissolved at room temperature for 1 h under nitrogen protection and mechanical stirring, and then 80 mL of 1-bromo-6-(trimethylammonium)hexyl bromide solution (prepared by dissolving 12.1 g of 1-bromo-6-(trimethylammonium)hexyl bromide in 80 mL of N, N-dimethylformamide) is added to the three-necked flask, the temperature is raised to 40° C. and stirred for 18 h, the solvent is removed by rotary evaporation, and the intercalant III is obtained after vacuum drying;

[0066] The nuclear magnetic resonance hydrogen spectrum characterization results of intercalant III are as follows: 1H NMR (DMSO-d6, 400MHz) δ: 0.81-1.03 (m, 16H), 1.33-1.87 (m, 80H), 2.52-2.80 (m, 24H), 2.98-3.02 (m, 8H), 3.11 (s, 72H), 3.32 (s, 8H), 3.59-3.69 (m, 16H). Embodiment 4:

[0067] Preparation of sodium mica: 20 g of sericite powder with a particle size of less than 10 μm is placed in a muffle furnace, heated to 80° C. for activation treatment for 1 hour, then the activated sericite powder is dispersed in 300 mL of a 5 mol / L nitric acid aqueous solution, heated to 90° C. and stirred for reaction for 5 hours for acidification treatment, centrifuged, washed with deionized water until neutral, and dried; the acidified sericite powder is dispersed in 300 mL of a saturated sodium chloride aqueous solution, heated to 95° C. and stirred for reaction for 4 hours for sodium treatment, allowed to stand overnight, centrifuged and washed until no precipitate is detected in the silver nitrate solution, and vacuum dried to obtain sodium mica;

[0068] (1) Preparation of intercalation modified mica I, wherein the preparation method is as follows: the ammonium cations of intercalation agent I react with the interlayer sodium cations of sodium mica through ion exchange reaction and then adsorb on the surface of mica sheets through electrostatic action to prepare intercalation modified mica I. The specific experimental steps are as follows: 10 g of sodium mica, 80 mL of methanol and 20 mL of N,N-dimethylformamide are added to a three-necked flask, ultrasonicated for 30 min, heated to 70 °C and stirred for 2 h, then 50 mL of intercalation agent I solution (prepared with 3.0 g of intercalation agent I, 20 mL of methanol and 30 mL of N,N-dimethylformamide) is added dropwise to the three-necked flask, stirred and reacted at 70 °C for 4 h, filtered while hot, washed with a mixed solution of methanol and N,N-dimethylformamide (the volume ratio of methanol to N,N-dimethylformamide is 2:3) until no precipitate is detected in the silver nitrate solution, vacuum dried and ground to obtain intercalation modified mica I;

[0069] An ethylene-vinyl alcohol copolymer / mica sheet composite material I is prepared, and the preparation method thereof is as follows: intercalation modified mica I is dispersed in an ethylene-vinyl alcohol copolymer matrix, the intercalation modified mica I contains an intercalation agent I, and the secondary amine functional groups on the intercalation agent I molecule and the hydroxyl functional groups contained in the ethylene-vinyl alcohol copolymer are hydrogen bonded to combine the ethylene-vinyl alcohol copolymer and the mica sheet to prepare the ethylene-vinyl alcohol copolymer / mica sheet composite material I, and the specific experimental steps are as follows: 15g of ethylene-vinyl alcohol copolymer and 5g of intercalation modified mica I are added into a twin-screw extruder, and the mixture is blended, melted, extruded, and pelletized by the twin-screw extruder to prepare the ethylene-vinyl alcohol copolymer / mica sheet composite material I;

[0070] (2) preparing intercalation-modified mica II, wherein the preparation method is as follows: the ammonium cations of intercalation agent II react with the interlayer sodium cations of sodium mica and then adsorb on the surface of mica sheets through electrostatic action to prepare intercalation-modified mica II. The specific experimental steps refer to the preparation experiment of intercalation-modified mica I, and the only difference is that intercalation agent II replaces intercalation agent I.

[0071] An ethylene-vinyl alcohol copolymer / mica sheet composite material II is prepared. The preparation method comprises the following steps: dispersing intercalation-modified mica II in an ethylene-vinyl alcohol copolymer matrix, wherein the intercalation-modified mica II contains an intercalation agent II, and hydrogen bonding occurs between the secondary amine functional groups on the intercalation agent II molecule and the hydroxyl functional groups contained in the ethylene-vinyl alcohol copolymer, thereby combining the ethylene-vinyl alcohol copolymer with the mica sheet to prepare the ethylene-vinyl alcohol copolymer / mica sheet composite material II. The specific experimental steps are based on the preparation experiment of the ethylene-vinyl alcohol copolymer / mica sheet composite material I, and the only difference is that the intercalation-modified mica II replaces the intercalation-modified mica I.

[0072] (3) preparing intercalation-modified mica III, wherein the preparation method is as follows: the ammonium cations of intercalation agent III react with the interlayer sodium cations of sodium mica and then adsorb on the surface of mica sheets through electrostatic action to prepare intercalation-modified mica III. The specific experimental steps refer to the preparation experiment of intercalation-modified mica I, and the only difference is that intercalation agent I is replaced by intercalation agent III;

[0073] An ethylene-vinyl alcohol copolymer / mica sheet composite material III is prepared. The preparation method comprises the following steps: dispersing intercalation-modified mica III in an ethylene-vinyl alcohol copolymer matrix, wherein the intercalation-modified mica III contains an intercalation agent III, and the secondary amine functional groups on the intercalation agent III molecule and the hydroxyl functional groups contained in the ethylene-vinyl alcohol copolymer are hydrogen-bonded to combine the ethylene-vinyl alcohol copolymer with the mica sheet, thereby preparing the ethylene-vinyl alcohol copolymer / mica sheet composite material III. The specific experimental steps are similar to the preparation experiment of the ethylene-vinyl alcohol copolymer / mica sheet composite material I, and the only difference is that the intercalation-modified mica III is used to replace the intercalation-modified mica I.

[0074] (4) preparing an ethylene-vinyl alcohol copolymer / mica flake blend material, wherein the preparation method is as follows: directly mixing sericite powder with a particle size of less than 10 μm with an ethylene-vinyl alcohol copolymer matrix to prepare an ethylene-vinyl alcohol copolymer / mica flake blend material, wherein the specific experimental steps refer to the preparation experiment of ethylene-vinyl alcohol copolymer / mica flake composite material I, and the only difference is that sericite powder is used to replace intercalated modified mica I;

[0075] The process parameters of the twin-screw extruder are set as follows: the temperatures of zones 1-3 are 150°C, 170°C, and 195°C, respectively, and the rotation speed is 40 r / min. Embodiment 5:

[0076] Preparation of symmetrical eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material: Design the film structure, formula and dosage of each film layer of the eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material (see Table 1 below for specific contents), and use an eleven-layer co-extruded film blow molding unit with the blowing ratio controlled at 2.6 to prepare eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material with a thickness of 100 μm.

[0077] Table 1 Experimental formula and process parameters of eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material

[0078]

[0079] Table 1 Experimental formula and process parameters of eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material

[0080]

[0081] Table 1 Experimental formula and process parameters of eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material

[0082]

[0083] When the ethylene-vinyl alcohol copolymer / mica sheet composite materials are ethylene-vinyl alcohol copolymer / mica sheet composite materials Ⅰ, Ⅱ, and Ⅲ, respectively, eleven layers of co-extruded high-barrier and high-strength recyclable liquid packaging materials Ⅰ, Ⅱ, and Ⅲ are prepared in sequence;

[0084] When the 5wt% ethylene-vinyl alcohol copolymer / mica sheet composite material is 2.5wt% ethylene-vinyl alcohol copolymer / mica sheet composite material II + 2.5wt% ethylene-vinyl alcohol copolymer / mica sheet composite material III, an eleven-layer co-extruded high-barrier high-strength recyclable liquid packaging material IV is prepared;

[0085] When the ethylene-vinyl alcohol copolymer / mica sheet blend material is used to replace the ethylene-vinyl alcohol copolymer / mica sheet composite material, an eleven-layer co-extruded high-barrier high-strength recyclable liquid packaging material a is prepared, which is used as comparative example 1;

[0086] When ethylene-vinyl alcohol copolymer is used to replace the ethylene-vinyl alcohol copolymer / mica sheet composite material, an eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material b is prepared, which is used as Comparative Example 2.

[0087] The specifications and manufacturers of the above-mentioned raw materials are shown in Table 2;

[0088] Table 2 Experimental raw materials

[0089]

[0090] Performance Test:

[0091] 1. Barrier performance test:

[0092] (1) Use the Y110 oxygen permeability tester to test the oxygen barrier properties of the sample in accordance with GB / T 1038-2000 and record the oxygen permeability of the sample;

[0093] (2) Use TC-03 water vapor transmission tester to test the water barrier properties of the sample in accordance with GB / T 1037-2021 and record the water vapor transmission rate of the sample;

[0094] 2. Mechanical properties:

[0095] The mechanical properties of the samples were tested using an Instron 5565 universal tensile testing machine. The specific test steps are as follows: a 150 mm × 20 mm sample was fixed on the tensile testing machine, and a tensile test was performed at a tensile rate of 5 mm / min, and the longitudinal and transverse tensile strengths of the samples were recorded;

[0096] The above experimental results are shown in Table 3.

[0097] Table 3 Performance test results of eleven-layer co-extruded high barrier and high strength recyclable liquid packaging materials

[0098]

[0099] According to the experimental data in Table 3, Figure 5 ,Through comprehensive analysis of the above experimental results, the following conclusions can be drawn:

[0100] The eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material prepared by modifying a single recyclable PE material using ethylene-vinyl alcohol copolymer / mica sheet composite materials I, II, and III has achieved a significant improvement in barrier properties and mechanical properties compared to the prior art.

[0101] Among them, the ethylene-vinyl alcohol copolymer / mica sheet composite material II (the ethylene-vinyl alcohol copolymer / mica sheet composite material obtained by modifying the intercalation agent containing double-sandwich structure cage-type silsesquioxane on the main chain) has a more significant effect on improving the mechanical properties of the eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material;

[0102] Ethylene-vinyl alcohol copolymer / mica sheet composite material III (ethylene-vinyl alcohol copolymer / mica sheet composite material obtained by using an intercalant modified with cage-type silsesquioxane (POSS) grafted with eight side chains and highly symmetrical structure) has a more significant effect on improving the barrier performance of eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging materials;

[0103] The synergistic combination of ethylene-vinyl alcohol copolymer / mica sheet composite material II and ethylene-vinyl alcohol copolymer / mica sheet composite material III can simultaneously improve the barrier properties and mechanical properties of the eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material.

Claims

1. A method for preparing an eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material. It is characterized in that The following steps are involved: Step 1: preparing an ethylene-vinyl alcohol copolymer / mica sheet composite material, wherein the preparation method of the composite material is as follows: (1) Thermal activation and structural modification of sericite to obtain sodium mica; (2) synthesizing an intercalation modification agent, wherein the intercalation modification agent is one or a combination of intercalation agent I, intercalation agent II, and intercalation agent III; Among them, intercalant I is a dibromide ammonium salt compound containing a long main chain and a secondary amine functional group, and its chemical structure is: ; Intercalant II is a dibromide ammonium salt compound containing a double-sandwich structure cage-type silsesquioxane and a secondary amine functional group on the long main chain, and its chemical structure is: ; Intercalant III is an ammonium octabromide salt compound in which eight long side chains are grafted onto a cage-type silsesquioxane POSS with a highly symmetrical spatial structure, and the long side chains contain secondary amine functional groups. Its chemical structure is: ; (3) The ammonium cations of the intercalation modification reagent undergo ion exchange reaction with the interlayer sodium cations of the sodium mica and then adsorb onto the surface of the mica sheet through electrostatic action to prepare intercalation modified mica with secondary amine functional groups; (4) dispersing the intercalated modified mica in the ethylene-vinyl alcohol copolymer, and combining the ethylene-vinyl alcohol copolymer with the mica sheet through hydrogen bonding between the secondary amine functional groups in the intercalated modified mica and the hydroxyl functional groups in the ethylene-vinyl alcohol copolymer, thereby preparing an ethylene-vinyl alcohol copolymer / mica sheet composite material; Step 2: Using polyethylene resin as a single raw material and ethylene-vinyl alcohol copolymer / mica sheet composite material as a functional modification agent, design the film structure of the eleven-layer co-extruded film, the formula and dosage of each film layer, and adopt an eleven-layer co-extrusion blow molding film forming process to prepare an eleven-layer co-extruded high-barrier, high-strength recyclable liquid packaging material.

2. The method for preparing an eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material according to claim 1, It is characterized in that The mass ratio of the intercalation modification agent to the sodium mica in the intercalation modified mica is (0.1-0.5):1; The particle size of the sericite is less than 10 μm.

3. The method for preparing an eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material according to claim 1, It is characterized in that The mass ratio of intercalated modified mica to ethylene-vinyl alcohol copolymer in the ethylene-vinyl alcohol copolymer / mica sheet composite material is 1:(0.5-5).

4. The method for preparing an eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material according to claim 1, It is characterized in that The content of the ethylene-vinyl alcohol copolymer / mica sheet composite material in the eleven-layer co-extruded high-barrier high-strength recyclable liquid packaging material is 0.5-2%.

5. The method for preparing an eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material according to claim 1, It is characterized in that The formula and dosage of each film layer of the eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material are as follows: First layer: The formula is 25~45wt% LDPE+25~45wt% LLDPE+10~50wt% m-LLDPE, and the dosage is 5~15wt%; The second layer: the formula is 25~45wt%HDPE+20~40wt%LLDPE+15~55wt%m-LLDPE, the dosage is 3~10wt%; The third layer: the formula is 10~30wt% LDPE+10~30wt% LLDPE+40~80wt% m-LLDPE, the dosage is 5~15wt%; The fourth layer: the formula is 100wt% PE-g-MAH, the dosage is 1~5wt%; The fifth layer: the formula is 95~99wt% LDPE+1~5wt% EVOH, the dosage is 5~15wt%; The sixth layer: the formula is 90~99wt% LDPE + 1~10wt% ethylene-vinyl alcohol copolymer / mica sheet composite material, the dosage is 10~40wt%; The seventh layer: the formula is 95~99wt% LDPE+1~5wt% EVOH, the dosage is 5~15wt%; The eighth layer: the formula is 100wt% PE-g-MAH, the dosage is 1~5wt%; Ninth layer: The formula is 10~30wt% LDPE+10~30wt% LLDPE+40~80wt% m-LLDPE, and the dosage is 5~15wt%; The tenth layer: the formula is 25~45wt%HDPE+20~40wt%LLDPE+15~55wt%m-LLDPE, the dosage is 3~10wt%; Eleventh layer: The formula is 25~45wt% LDPE+25~45wt% LLDPE+10~50wt% m-LLDPE, and the dosage is 5~15wt%.

6. The method for preparing an eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material according to claim 1, It is characterized in that The preparation method of the intercalant I is as follows: using 1,3-propylenediamine and 1-bromo-6-(trimethylammonium)hexyl bromide as raw materials, and preparing the intercalant I by a substitution reaction between the bromine functional group of 1-bromo-6-(trimethylammonium)hexyl bromide and the amino functional group of 1,3-propylenediamine.

7. The method for preparing an eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material according to claim 1, It is characterized in that The preparation method of the intercalant II is as follows: Step S7-1: preparing a synthetic amino-terminated octaphenyl cage silsesquioxane monomer by an addition reaction between the Si—H bond of the octaphenyl cage silsesquioxane and the alkenyl functional group of 3-butene-1-amine; Step S7-2: using the amino-terminated octaphenyl cage silsesquioxane monomer as a nucleophilic reagent, the bromine functional group of 1-bromo-6-(trimethylammonium)hexyl bromide and the amino functional group of the amino-terminated octaphenyl cage silsesquioxane monomer undergo a substitution reaction to prepare an intercalant II.

8. The method for preparing an eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material according to claim 1, It is characterized in that The preparation method of the intercalant III is as follows: the bromine functional group of 1-bromo-6-(trimethylammonium)hexyl bromide and the amino functional group of octaaminopropyl POSS undergo a substitution reaction to prepare the intercalant III.

9. An eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material prepared according to the method of any one of claims 1 to 8, It is characterized in that The thickness of the eleven-layer co-extruded high-barrier and high-strength recyclable liquid packaging material is 50-200 μm.

10. The eleven-layer co-extruded high-barrier, high-strength, recyclable liquid packaging material according to claim 9, It is characterized in that The eleven-layer co-extruded high-barrier, high-strength and recyclable liquid packaging material is used in the field of liquid packaging.